Bioaugmentasi Benzena Tanah Tercemar Hidrokarbon yang Dibiodegradasi secara in vitro dengan Menggunakan Bacillus Sp. Strain U41 dan U44 - Irianto, Agus; Oedjiono, Oedjiono; Riyanto, Agus; Komar, M. Syamsul (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2003)
Soil pollution by substances such as benzene can cause serious problems such as aquifer contamination and reduction of the biodiversity of organisms. A number of microorganisms are capable to degrade such substances naturally. However, introduction of any other microorganisms and or nutrient (bioaugmentation) are necessary in order to improve the biodegradation rate. This study examined the effect of introducing promising local strains of Bacillus namely U41 and U44, and urea addition at concentration 0.25% w/v. The parameter measured was benzene, pH, microbial number, and CO2. The best result was revealed from bioaugmentation of mixture of U41 and U 44. However, that result was not significantly difference with the use of single either strain U41 or U44, respectively.